Karakteristik Pasien Luka Bakar di Rumah Sakit Ibnu Sina, Gresik, Indonesia – 2022–2024: Sebuah Studi Deskriptif Observasional Retrospektif: Penelitian - Rahman, Akhmad Setyo; Harijanto, Taufan; Marsetio, Dono; Negara, Agung Kusuma; Fadhilah, Nur Lailatul (Cermin Dunia Kedokteran, 2026)
Introduction: Burns are a significant cause of morbidity and mortality, particularly in developing countries with limitations in healthcare systems. This study describes clinical characteristics of burn patients at Ibnu Sina Regional Public Hospital, Gresik Regency, during the2022−2024 period. Methods: A retrospective observational descriptive study on secondary data from medical records of burn patients admitted through the Emergency Department (ED) within the first 24 hours following injury. Results: Out of a total of 64 patients, the majoritywere male and within the productive age group (16−35 years). Most worked as entrepreneurs or factory workers. The most frequent causes of burns were flame exposure and gas explosions, mostly involving 20%−39% of the total body surface area (TBSA). Patients with inhalationtrauma and comorbidities, such as diabetes mellitus or smoking habits, experienced longer hospital stays. Conclusion: Most moderate-tosevere burn injuries in this study occurred among factory workers and entrepreneurs as a result of open flame and gas explosions, indicatingthe need to strengthen occupational safety and burn prevention efforts in the workplace.